PENGARUH WORKING CAPITAL TURNOVER (WCT) DAN DEBT TO EQUITY RATIO (DER) TERHADAP RETURN ON ASSETS (ROA) PADA PT. MUSTIKA RATU TBK - NABILLA SELVILAM SA’IDAH; NURUL HUDA; JUWANI JUWANI (Universitas Mahasaraswati K. Mataram, 2024)
This research aims to examine the influence of Working Capital Turnover (WCT) and Debt To Equity Ratio (DER) on Return On Assets (ROA) at PT. Mustika Ratu Tbk during the period from 2011 to 2022. The data used in this study are secondary data in quantitative form. The research instrument used includes tables covering current assets, total assets, current liabilities, total liabilities, total equity, sales, and net profit after tax. The population for this study covers 15 years (2008-2022), with a sample of 12 years (2011-2022). The sampling technique used is purposive sampling. Data collection methods involve documentation and literature review. The data analysis techniques employed include classical assumption tests, multiple linear regression, t-tests, and F-tests.The results of the analysis indicate that WCT has a significant partial effect on ROA, suggesting that the efficiency of working capital utilization affects the company's ability to generate profit from its total assets. Additionally, DER also has a significant partial effect on ROA, indicating that the company's capital structure influences its profitability. WCT and DER together have a significant simultaneous effect on ROA. This study contributes to understanding the factors influencing corporate financial performance and their relevance in managerial decision-making.